PARADIGMA REVOLUSI MENTAL DALAM PEMBENTUKAN KARAKTER BANGSA BERBASIS SINERGITAS ISLAM DAN FILSAFAT PENDIDIKAN - Maragustam Maragustam (Jurnal Pendidikan Agama Islam, 2015)
Mental revolution associated with a massive revamp of the human mind which manifests in three mindset patterns, confident, and patterns of taste-spirituality that bear behavior. That three patterns were based on the values that is planted in a person, they are: religion, culture-tradition, and philosophy of the nation. The existence of a person’s mental character is influenced by many factors, namelyeducation, environment, heredity and global culture. The global culture is useful to make everything easier to do in all areas of life, but on the other hand, the negative impact of global culture created secularism, materialism, hedonism, liberalism and the absence of religious spirituality. Therefore, this research attempts to answer how does the mental revolution paradigm toward characer establishment that based on the synergy of Islam and educational philosophy, how the strategy implies, and which values are needed to be revolutionized primarily. The approach is qualitative-reference by using analysis technique such as : content analysis, data reduction, data display and data verification. The conclusion is that a paradigm of mental revolution is basically the positive (good)-interactive mental of human and also dual-interactive. Mental revolution should be carried through stages and lasting continuously through six holistic and integral pillars:civilizing-habituation, moral knowing, moral loving and feeling, moral acting, modelling and conversion to implement takhalli, tahalli and tajalli.